PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT TUMBUH SUKSES NASTARI KABUPATEN BOGOR - Muhammad Rifqi Iskandar; Irfan Rizka Akbar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to determine and analyze the influence of work discipline and physical work environment on employee performance at PT Tumbuh Sukses Nastari, Bogor Regency. The population in this study were 50 employees of PT Tumbuh Sukses Nastari, Bogor Regency. The sampling method in this study used saturated sampling techniques, data analysis methods used were descriptive statistical tests, instrument tests (validity tests and reliability tests), classical assumption tests (normality tests, multicollinearity tests, and heteroscedasticity tests), correlation tests, coefficient of determination tests, regression tests, and hypothesis tests using SPSS Ver.25. The results of this study are that Work Discipline has a significant effect on employee performance with a coefficient of determination of (30.6%), and the hypothesis test obtained a calculated t value> t table or (4.604>1.677). The work environment has a significant effect on employee performance with a coefficient of determination of (36.3%) and the hypothesis test obtained a calculated t value> t table or (5.230>1.677). Work discipline and work environment have a significant simultaneous effect on employee performance with the regression equation Y = 7.355 + 0.315X1 + 0.457X2, the coefficient of determination value is (40.3%) while the remaining (59.7%) is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (15.800 > 3.200). Keywords: Work discipline, Physical work environment, Employee performance